2023
DOI: 10.1108/tqm-11-2022-0322
|View full text |Cite
|
Sign up to set email alerts
|

The effect of accreditation on higher education performance through quality culture mediation: the perceptions of administrative and quality managers

Abstract: PurposeThis study aims to examine the effect of accreditation on higher education performance, directly and indirectly, through the quality culture as a mediator in the context of higher education, based on the perceptions of administrative and quality managers.Design/methodology/approachThis is a quantitative study using stratified random sampling techniques to collect data through a nationwide survey of universities in Pakistan. Of the 150 questionnaires distributed, 105 are found to be valid, while the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Furthermore, QC as a dynamic ability was found to play a significant role both as a predictor of OP and as a mediator in the relationship between TFL, TNL and OP, aligning with DCT principles. While some recent studies have examined the mediating effect of QC (Iqbal et al , 2023b; Iqbal et al , 2023c), no previous research has investigated QC as a mediator in the relationship between TFL, TNL and OP in the context of HE. Therefore, this study provides novel insights into the crucial role of QC as a dynamic capability that acts as both a predictor and mediator, enhancing quality and OP and ultimately leading to a competitive advantage.…”
Section: Data Analysis Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, QC as a dynamic ability was found to play a significant role both as a predictor of OP and as a mediator in the relationship between TFL, TNL and OP, aligning with DCT principles. While some recent studies have examined the mediating effect of QC (Iqbal et al , 2023b; Iqbal et al , 2023c), no previous research has investigated QC as a mediator in the relationship between TFL, TNL and OP in the context of HE. Therefore, this study provides novel insights into the crucial role of QC as a dynamic capability that acts as both a predictor and mediator, enhancing quality and OP and ultimately leading to a competitive advantage.…”
Section: Data Analysis Results and Discussionmentioning
confidence: 99%
“…Several researchers have examined QC primarily as a predictor variable (Hilman et al, 2017;Iqbal et al, 2023b;Wu, 2015), or, in a few cases, as a criterion variable (Herminingsih et al, 2020). However, there have been limited studies investigating QC as a mediator in the context of HE, and their results confirmed the mediating effect of QC on the relationship between accreditation and HE performance (Iqbal et al, 2023c), and the relationship between intrinsic motivation, extrinsic motivation and HE performance (Iqbal et al, 2023a). Nevertheless, there is a gap in the existing literature regarding the investigation of QC as a mediator between TFL, TNL and OP.…”
Section: Mediating Role Of Quality Culturementioning
confidence: 99%
See 3 more Smart Citations